LAVINIA F - THE FIRST ROMANIAN WINTER PEA CULTIVAR CREATED AT NATIONAL AGRICULTURAL RESEARCH AND DEVELOPMENT INSTITUTE FUNDULEA, ROMANIA - Ancuţa BĂRBIERU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Lavinia F is a winter pea (Pisum Sativum L.) cultivar created at National Agricultural Research and Development Institute Fundulea (NARDI), egistered in 2020 and obtained through sexual hybridization and selected by pedigree method from Dorica/Checo hybrid population. The new ntry is of aphyla type, with an early vegetation period, of 213-216 days. Is was released based on superior agronomic adaptation, winter ardiness and tolerance to harsh winter condition. The plant height ranges between 70 and 90 cm, with a good resistance to lodging, better esistance to diseases, drought and pests. The flower color is white, with spherical, smooth grains and yellow pericarp. It is a high yield ariety with an improved level of quality. A good yield potential was estimated in newly developed Lavinia F cultivar 4210 kg/ha in 2018 and 017 kg/ha in 2019, in Ludus. The Thousand Grains Weight (TGW) of the winter pea cultivar analysed during 2018-2019 varied between 204 g ( ogealac) and 235 g (Luduș) in 2018, and in 2019 between 166 g (Negresti) and 229 g (Inand). The objective of the present study was to escribe a new culture in Romania, which is sowed in autumn, namely Lavinia F the new cultivar of winter pea. The results presented in this paper show that the first cultivar of winter pea is adapted to climate conditions in Romania and will be a new hallenge for farmers.